An empirical study of moral reasoning among managers - Derry, Robbin (Journal of business ethics, 1989)
Current research in moral development suggests that there are two distinct modes of moral reasoning, one based on a morality of justice, the other based on a morality of care. The research presented here examines the kinds of moral reasoning used by managers in work-related conflicts. Twenty men and twenty women were randomly selected from the population of first level managers in a Fortune 100 industrial corporation. In open-ended interviews each participant was asked to describe a situation of moral conflict in her or his work life. The results indicated a clearly preferred mode of moral reasoning among the participants who described moral conflicts. Nearly all of these predominated with a justice orientation. These findings suggest that a correlation between gender and preferred mode may be context specific.